WEB-BASED CRM APPLICATION WITH CUSTOMER ELIGIBILITY SIMULATION FEATURE USING EXPONENTIAL COMPARISON METHOD AT KOPERASI NUSANTARA MANDIRI - Benyamin, Evan; Chasanah, Nur; Ekowati, Nur Alfi (Informatika, Universitas Jenderal Soedirman, 2024)
In the competitive and dynamic digital era, cooperatives must have systems that accommodate both operational needs and customers to improve service quality and customer satisfaction. However, Koperasi Nusantara Mandiri in Bandung Regency does not yet have a system that encompasses both aspects, rendering the cooperative's services ineffective and less competitive. Therefore, the cooperative requires a Customer Relationship Management (CRM) system to assist potential customers by providing loan eligibility calculation simulations. This research aims to implement a decision support method in a system using the waterfall methodology, which includes the stages of requirements, design, implementation, testing, and maintenance to develop a web-based CRM application. The application is designed and developed to help the cooperative manages the customer data, ease the business processes, and enhance effectiveness in both operations and customer analysis. Testing is conducted using the black box technique to ensure the application meets the specified requirements. The research results indicate that the developed CRM application functions well and meets the needs of Koperasi Nusantara Mandiri, thereby increasing the cooperative's operational effectiveness.